MUNDOS VIRTUALES INMERSIVOS PARA EDUCACIÓN, TRABAJO COLABORATIVO Y SIMULACIÓN (2013)
Being able to observe the customs of teenagers and young adults known as ``digital natives'' has helped in understanding how they enjoy playing in simulated worlds. During the virtual gatherings, they are able to connect with strangers while collaborating, generating strategies and employing a significant amount of time towards common goals. Consequently, the software industry works in building platforms for virtual worlds and the education industry has begun to analyze how to take advantage of these platforms for education purposes. These worlds, materialized as multi-user software, enable each participant, represented by an avatar, to be part of a 3D environment in which the interaction takes place by text or voice chat. In these worlds, it is possible to develop learning, socializing, simulation and immersion activities in situations pedagogically developed, so that each user can observe, interact, and make decisions virtually.This paper illustrates three case studies about virtual worlds with educational purposes. The first case study is about learning activities regarding the international humanitarian law; for this case study, the paper illustrates how the instructional design was carefully done.During the instructional design and the development of the learning experience, the need for tools supporting collaborative construction in the virtual world was identified, giving birth to a new project, which makes the second case study of the paper. The goal of this project was to develop tools for building concept maps and notes board virtually. The third case study is about using virtual worlds for simulating natural disasters situations such as, for instance, earthquakes.